Pesticides, volatile and semivolatile organic compounds in the inland surface waters of Cyprus - Fatta-Kassinos, Despo; Michael, C.; Canna-Michaelidou, Stella; Christodoulidou, Maro; Kythreotou, Nicoletta; Vasquez Christodoulou, Marlen (My University, 2007)
The pollution of the surface waters of Cyprus from priority compounds which are included in the EU Directive 76/464/EEC was evaluated. The Directive deals with the pollution caused by certain dangerous substances discharged into the aquatic environment of the Community. In the framework of the reporting obligations of Cyprus towards EU, a study was carried out for the Environment Service of Cyprus by the University of Cyprus in collaboration with the State General Laboratory. 19 out of the 59 surface water bodies of the country were investigated. 30 substances of List I, List I candidates and List II were examined. The analytical determination was performed by a Gas Chromatography - Electron Capture Detection for organochlorine insecticides, by Gas Chromatography - Flame Thermionic Detector for the chlorotriazine herbicides and organophosphate insecticides and finally by on line purge and trap technique followed by Gas Chromatography - Electron Capture Detection/Photoionization Detection for the volatiles and semivolatiles organic compounds. Toluene, 1,1,1-trichloroethane, 1,2-dichloropropane, vinyl chloride and 1,4-dichlorobenzene were the most frequently found among VOCs and SVOCs. In some cases non-compliance was observed for hexachlorobutadiene, hexachlorobenzene and 1,2,4- trichlorobenzene. The most commonly encountered organochlorine insecticides were hexachlorobenzene and heptachlor. This paper summarizes the work carried out, the methodologies applied and provides a discussion on the results found.
Keywords: Cyprus surface waters; Pesticides; Volatile and semivolatile compounds; GC-FTD; GC-ECD; On-line purge and trap — GC-ECD/PID